Other side of the Ashulia wetland: a limnological purview - Hossain Bhuiyan, M Azmal; Khondker, Moniruzzaman; Begum, ZN Tahmida (Dhaka University Journal of Biological Sciences, 2011)
Limnology of a temporary wetland Ashulia was found highly seasonal. Fluctuations of water depth, water temperature, Secchi depth, pH, conductivity, total dissolved solids, dissolved oxygen and alkalinity were studied in three different stations for one year. Water depth showed a range of 1.5 - 4.2 m and Secchi disc transparency from 0.07 - 2.15 m. Annual ranges in respect of pH, conductivity, total dissolved solids (TDS), dissolved oxygen (DO) and alkalinity of water varied from 6.3 -7.2, 92 - 1028 μS/cm,43.4 - 491.0 mg/l, 4.3 - 28.9 mg/l, and 0.71 - 6.45 meq/l, respectively. The wetland showed a good to moderate water quality during rainy season because in this season visibility of water increased, TDS load, alkalinity and conductivity came down to their lowest. Dissolved oxygen content also showed an acceptable water quality value during rainy season. Key words: Wetland; Physical factors; Chemical factors; Limnology; Phytoplankton; Macrophytes DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8940 DUJBS 2010; 19(1): 21-26